Eco-efficiency assessment for global warming potential of ethylene production processes: A case study of China. (20th January 2017) - Chen, Qianqian; Lv, Min; Wang, Danfeng; Tang, Zhiyong; Wei, Wei; Sun, Yuhan
Abstract: Ethylene, as one of the demanding basic chemical materials, contributes to China's energy consumption and carbon emission during its production process. The research analyses eco-efficiency of various ethylene production routes from the sustainability perspective. The net value added of ethylene product is used as the economic indicator while the life cycle greenhouse gas emission is used as environmental indicator. Three ethylene production routes are set as follows: 1) OTO route (oil-to-ethylene) - using crude oil imported from Middle East as raw material to produce ethylene in eastern China; 2) NTO route (natural gas-to-ethylene) – using American natural gas/shale gas to produce methanol→importing methanol to eastern China→methanol-to-ethylene; 3) CTO route (coal-to-ethylene) – using coal to produce methanol in western China→transporting methanol to eastern china→methanol-to-ethylene. Among them, NTO leads to the highest net value added of ethylene product and lowest life cycle GHG emission. And the eco-efficiency of NTO is 30.2% and 176.6% higher than OTO and CTO, respectively. The integration of carbon capture and storage (CCS) unit with CTO can reduce the carbon emission, but nonetheless, the eco-efficiency of CTO-CCS is still 31–47% lower than the other two production routes even considering 90% carbon capture ratio. Based on the assessment above, the NTO production route is the most economical and environmental friendly, it shall have greater potential for China ethylene market. Highlights: Eco-efficiency of various ethylene production routes is evaluated. Natural gas-to-ethylene route has the lowest life cycle GHG emission. Natural gas-to-ethylene route has the best economic performance. Coal-to-ethylene is not competitive even with carbon capture and storage unit.